Restaurant innovativeness: A case study of Vojvodina - Gagić, Snježana (The European Journal of Applied Economics, 2016)
It is of vital importance to continuously work on the improvement and identification of significant factors to ensure and sustain the desired level of quality. The paper aims to analyze the innovativeness level of restaurants in Vojvodina in view of the fact that it keeps their portfolio competitive and thereby achieves a long-term competitive advantage. The innovativeness level was defined on the basis of the instrument designed for measuring innovation in the field of products and services, marketing, processes and socially responsible behavior. In order to determine the level of innovativeness, it was necessary to first determine the percentage of innovativeness based on the number of innovations introduced by the restaurants in all of the four study areas. The results show that a significant number of restaurants pays attention to innovations in order to become more appealing to guests and increase their profitability. On the other hand, more than half of the observed restaurants have a very low or low degree of innovation, which indicates that we still do not pay enough attention to innovations and advancement of their business implementation.
Keywords: service innovations; restaurant marketing innovations; gastronomic trends; restaurant innovation